Explorative study on the antibacterial effects of 3D-printed PMMA/nitrides composites. (August 2021) - Marin, Elia; Boschetto, Francesco; Zanocco, Matteo; Honma, Taigi; Zhu, Wenliang; Pezzotti, Giuseppe
Graphical abstract: Highlights: PMMA/nitride composites were successfully applied to 3D printed PMMA components. All nitrides showed a certain degree of antibacterial effects against E coli and S epidermidis . Hf3 N4, Zr3 N4 and AlN showed promising potential as antibacterial materials. The mechanism of action of Hf3 N4 and Zr3 N4 is not based on the release of NH3, unlike Si3 N4 and AlN. Abstract: Following the rising interested on 3D-printing technologies, this research explores the possibility to apply nitride-polymethylmethacrylate composite coatings on 3D printed parts in order to increase their resistance to bacteria colonization. Four different nitrides were tested: silicon, zirconium, hafnium and aluminum. Trans-micrometric particles of hafnium nitride (average size 1 µm) could be dispersed better than the other three nitrides (average size between 8 and 10 µm), but the chemical analysis confirmed that the former, due to the higher surface area, are more prone to spontaneous oxidation in air. After deposition, the surface of the various coatings contained between 40% (silicon nitride) and 90% (hafnium nitride) of exposed ceramic particles. All composite materials showed antibacterial effects when compared to standard polymethylmethacrylate, with hafnium nitride being the most effective against E. coli and aluminum nitride against S. epidermidis . It has been postulated that while Si3 N4 long-term antibacterial effects are granted by the constant dissolution of the SiO2 surface layer, zirconium and hafnium composites are effective because they possess antibacterial properties both in their nitride and oxide forms.